NU DAN PROBLEM KEMISKINAN (Upaya Pemberdayaan Ekonomi dan Kesejahteraan Masa Kolonial) - Kholid Mawardi (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2013)
This paper explained how Nahdlatul Ulama (NU) preceive poverty. As thebiggest social organization, its members are spread out all over Indonesia,especially those from pesantren background. Seen from the geographical areas,most of pesantren are located in rural areas, which is economically identical withthe areas of poverty. Accordingly, many of NU members belongs to this category.The futuristic view of NU are facing the reality of its members who hassome limitations of economy, politics, and education. Based on this view, NU hasa lot of dynamics, such as the development of tits young leader’s way of thinkingthat are different from the mainstream. The liberal image of its young leader’sway of thinking indicates that this organization has very dynamic movements.